Rapidly Progressing Primary Spondylodiscitis Due to Aeromonas hydrophila in an Immunocompetent Adult: A Case Report and Review of Literature - Vinod V. Rajan; Midhun Madhavan; Anith T. Venu; Rakesh T. Parakadavathu (Indian Spine Journal)
We describe a case of primary cervical spondylodiscitis accompanied by myeloradiculopathy, produced by Aeromonas hydrophila in an otherwise healthy individual. The patient presented with acute onset of cervical myelopathy and magnetic resonance imaging (MRI) cervical spine showed infective spondylodiscitis. The patient underwent cervical discectomy, debridement, and stabilization. Intraoperative findings were consistent with an infective process and cultures grew A. hydrophila. Patient was treated with sensitive antibiotics for 3 months leading to complete recovery. This is the first time that primary cervical spondylodiscitis by Aeromonas is reported, all other cases being secondary.